2018
DOI: 10.17843/rpmesp.2018.352.3352
|View full text |Cite
|
Sign up to set email alerts
|

Perspectivas metodológicas de la investigación en salud pública, breve mirada

Abstract: Research allows for the strengthening of disciplines, particularly those that draw on information from various specialties, such as public health. The objective of this report is to provide consolidated methodological perspectives to enrich public health as a science. The review highlights three key elements: the type of investigative approach, the evidence and competence approaches in the methodological context of the inquiry into collective health. It is concluded that the systematic, specific knowledge, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…The calculated average of hemoglobin in the third trimester is 11.89 g/dl, lower than that reported by Quispe [24] which was 12.7 g/dl in the city of Puno in 2016, it could be due to the geographical location that is so different from both studies (jungle and highlands); also in the scope of study according to NAS, 80% of pregnant women have some degree of anemia; it is important to reflect that the hemoglobin of the third trimester of the pregnant woman does not support the physiological blood loss of childbirth, as a consequence, it is decreased in the postpartum period falling to 10.37 g/dl, the value corresponds to a mild anemia, this difference is statistically significant at a p-value of 0.05, the decrease occurred in 1.52 g/dl, a value that is located in the 50th percentile due to the table of quantification of blood loss made by Rubio [11], although it is true that the difference in hemoglobin is not yet classified as a considerable loss that could be a hemorrhage. Hemoglobin in the immediate puerperium is a figure that is considered mild anemia [14], this is due to the hemoglobin in the third trimester is also not optimal to face childbirth; this finding leads us to the need to strengthen the development of anemia prevention strategies in pregnancy in accordance with the current national plan [22], in such a way that the pregnant woman enters to childbirth with a reserve that can make blood loss bearable than physiologically that happens in childbirth and the immediate puerperium. Vaginal childbirth is an event where less blood is lost, a maximum of 500 ml, therefore it is expected that the difference found will be less than high birth, in our study, it found hemoglobin of the third trimester of pregnancy at 11.90, and 10.65 g / dl in the immediate puerperium, while Atero [25] finds higher figures than the study presented, during the third trimester registering 12.87 ± 1.16 g/dl and it was 11.75 ± 1.67 g/dl in the immediate puerperium, however Ayllon, et al [26] in 1989 at the Maternal Perinatal Institute of Lima found lower prepartum figures 10.89 ± 1.57gr% and it was 9.95 ± 1.59 gr% in the postpartum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated average of hemoglobin in the third trimester is 11.89 g/dl, lower than that reported by Quispe [24] which was 12.7 g/dl in the city of Puno in 2016, it could be due to the geographical location that is so different from both studies (jungle and highlands); also in the scope of study according to NAS, 80% of pregnant women have some degree of anemia; it is important to reflect that the hemoglobin of the third trimester of the pregnant woman does not support the physiological blood loss of childbirth, as a consequence, it is decreased in the postpartum period falling to 10.37 g/dl, the value corresponds to a mild anemia, this difference is statistically significant at a p-value of 0.05, the decrease occurred in 1.52 g/dl, a value that is located in the 50th percentile due to the table of quantification of blood loss made by Rubio [11], although it is true that the difference in hemoglobin is not yet classified as a considerable loss that could be a hemorrhage. Hemoglobin in the immediate puerperium is a figure that is considered mild anemia [14], this is due to the hemoglobin in the third trimester is also not optimal to face childbirth; this finding leads us to the need to strengthen the development of anemia prevention strategies in pregnancy in accordance with the current national plan [22], in such a way that the pregnant woman enters to childbirth with a reserve that can make blood loss bearable than physiologically that happens in childbirth and the immediate puerperium. Vaginal childbirth is an event where less blood is lost, a maximum of 500 ml, therefore it is expected that the difference found will be less than high birth, in our study, it found hemoglobin of the third trimester of pregnancy at 11.90, and 10.65 g / dl in the immediate puerperium, while Atero [25] finds higher figures than the study presented, during the third trimester registering 12.87 ± 1.16 g/dl and it was 11.75 ± 1.67 g/dl in the immediate puerperium, however Ayllon, et al [26] in 1989 at the Maternal Perinatal Institute of Lima found lower prepartum figures 10.89 ± 1.57gr% and it was 9.95 ± 1.59 gr% in the postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…The type of research was observational, a secondary source was used for the collection of information, so is classified as a retrospective longitudinal section of a related sample, because the hemoglobin data is collected in the third trimester and in the immediate postpartum of the pregnancy of same pregnant woman [22]. When the researchers collect the information of the object of study as it happens in reality and is limited only to observe and describe the phenomenon, the descriptive level is attributed to it, in this case the maternal hemoglobin is studied at two crucial moments such as when it ends pregnancy and immediate postpartum [23].…”
Section: B Design and Populationmentioning
confidence: 99%
“…The process of research and dissemination of scientific knowledge is crucial for the strengthening, development, and advancement of scientific disciplines, especially those that are nourished by the integration of several specialties, as is the case of public health, where its foundations and competencies are not governed by mere intuition or empiricism in itself, but, on the contrary, arise from a methodological and conceptually sound framework [1,2]. Public health research is the most direct and truthful form of communication about the development of a country and is of great help in the case of developing countries, since in these, decision-making in public health is strongly influenced by empirical thoughts and assumptions made by politicians about the state of the population [3].…”
Section: Introductionmentioning
confidence: 99%
“…Public health research is the most direct and truthful form of communication about the development of a country and is of great help in the case of developing countries, since in these, decision-making in public health is strongly influenced by empirical thoughts and assumptions made by politicians about the state of the population [3]. In view of this, evidence obtained through the scientific method represents the best way to promote decision-making in accordance with the reality of a population [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation